el testamento cerrado, la apertura, publicación y sus efectos con las últimas reformas - Valle Suárez, Luis Francisco (2024)
In Ecuadorian legislation, there are two ways to succeed the hereditary rights of the deceased person or people; the first one is through a will, and the second one is intestate that comes from Latin and means without a will. This research is a reason for analysis on the closed will when there is opposition from an heir or any person that has the right. About this topic, there are reforms to the Civil code, Notarial Law, and General Organic Code of Processes but this figure is not well-known and used by citizens in Ecuador; for this reason, a critical-juridical analysis should be carried out on the procedure to follow for the case of a testamentary succession in the specific case of a closed will with opposition so that there is not any legal uncertainty that harms those who are beneficiaries or heirs through this legal figure. The applied methodology was under a mixed approach through a descriptive scope. The main results of research identify high level of ignorance about the topic and the processes to be followed by the citizenship in the cases of the type studied. There is not a will culture in society; there are flaws in people training from the implications of the educational system in terms of the necessary legal culture. Currently, actions and policies carried out and established by both the Constitution and the Labor Code have allowed people who suffer any catastrophic disease to enjoy special protection which is differentiated in both the work and social environment because their condition is a double vulnerability, and it allows them to access better and optimal conditions for a better life quality. Notwithstanding the above, regarding the labor environment, there are still legal loopholes specially in the Labor Code that does not protect the workers who suffer certain catastrophic diseases since they are sometimes the target of multiple discriminations putting at risk not only their health but their labor stability, too; on the other hand, regarding this topic, this Code establishes the ways to end a work contract in which eviction is one of them, which allows both the employer and the employee to make voluntary agreements to avoid labor conflicts or untimely dismissals. Therefore, it is necessary to implement a labor reform that allows employers to be able to voluntarily terminate their labor contract because they are suffering a catastrophic disease since it affects physical and emotional health of people causing their work performance to be affected, given that a sound and healthy employer is not the same as an ill employer; for this reason, several employers choose to resign and fully dedicate themselves to recover their health without resulting in a cause for their rights and labor guarantees not to be respected and to receive corresponding compensations that law grants them for their double vulnerability condition.